Railway station to improve transportation urban passenger District Coronel Gregorio Albarracin Lanchipa - Coaquera Mayta, Milena Yesenia (2017)
The evolution of the city of Tacna and its projections in the national and international scope in the matter of the railway development has gone back importance in the last years; Contemplating the proposal of a new railway station in the grounds of the ZOTAC, it is proposed that it be articulated to a central railway station, with the use of existing rail networks, focused on the connectivity of the urban areas with the highest population growth in the city , The center of Tacna and Coronel district Gregorio Albarracin Lanchipa, in response to the growing demand for public transpon. Objective: The present research a ims to propose and develop the architectural design of a central railway station to improve the urban transportation of passengers of the district Coronel Gregorio Alba rracín Lanchipa. Method: The research is of a project type, generating knowledge from the project, because it isolates the variables and indicators to provide innovative solutions in response to latent problems of society. Result: As a result of the research, the railroad central station a rchitectura I project was developed to improve the urban passenger transport of the Colonel Gregorio Albarracín Lanchipa district, considering its respective socioeconomic and urban environmental basis. Conclusion: The central railway station provides an alternative to conventional transportation, with the versatility of integrating with the existing transport system and with the option of projecting to the rest of the city by means of high capacity and lowerenvironmental impact.